Growth in the association between dimensions of antisocial thought process over time and in relation to delinquent involvement: a study of early adolescent youth - Walters, Glenn D. (Psychology, crime & law, 2024)
The goal of this study was to determine whether the relationship between cognitive insensitivity and cognitive impulsivity, two core dimensions of antisocial thought process, grew significantly over a period of two years and whether this growth was more evident in actively delinquent youth. A group of 845 adolescent male and female middle-school students completed measures of cognitive insensitivity and impulsivity at three points in time, with one year between each point or wave. Analyses were conducted using the Fisher r-to-Z transformed Pearson-Filon statistic for comparing nonoverlapping dependent correlations. Analyses showed that the correlation between cognitive insensitivity and cognitive impulsivity increased significantly from Wave 1 to Wave 3. When analyses were performed separately for youth displaying above average and below average delinquency across the three waves, significant increases occurred only in the subgroup with above average delinquency scores and then only between Waves 2 and 3 and then between Waves 1 and 3. These findings suggest that the cognitive insensitivity and impulsivity dimensions of antisocial thought process become increasingly more intertwined as youth move through early adolescence, but only in youth who display regular involvement in delinquency over time.